2020
DOI: 10.3390/nano10122486
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Imaging of Encapsulated Superparamagnetic Nanoparticles by Data Fusion of Magnetic Force Microscopy and Atomic Force Microscopy Signals for Correction of Topographic Crosstalk

Abstract: Encapsulated magnetic nanoparticles are of increasing interest for biomedical applications. However, up to now, it is still not possible to characterize their localized magnetic properties within the capsules. Magnetic Force Microscopy (MFM) has proved to be a suitable technique to image magnetic nanoparticles at ambient conditions revealing information about the spatial distribution and the magnetic properties of the nanoparticles simultaneously. However, MFM measurements on magnetic nanoparticles lead to fal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…Both contributions are taken into account in the phase shift equation for lift mode measurements in table 2 left column, which gives the phase signal as a function of the topographic parameter and the dielectric constant. In this paper, we use a parabolic tip model as described in our previous works in order to calculate A eff [9,18]. Measurements in lift mode always include contributions from the topography, reducing the sensitivity to determine the dielectric contrast and even falsifying the results.…”
Section: Dielectric Contrast Of Non-planar Surface Structures In Lift...mentioning
confidence: 99%
See 1 more Smart Citation
“…Both contributions are taken into account in the phase shift equation for lift mode measurements in table 2 left column, which gives the phase signal as a function of the topographic parameter and the dielectric constant. In this paper, we use a parabolic tip model as described in our previous works in order to calculate A eff [9,18]. Measurements in lift mode always include contributions from the topography, reducing the sensitivity to determine the dielectric contrast and even falsifying the results.…”
Section: Dielectric Contrast Of Non-planar Surface Structures In Lift...mentioning
confidence: 99%
“…In order to investigate the magnetism of nanoparticles, it was shown that while embedding the nanoparticles, the crosstalk due to capacitive coupling disappears [17]. In earlier work [18], an algorithm was developed to correct MFM lift mode data based on a correlation of the AFM signal and the MFM signal. A similar method was developed by van der Hofstadt for lift mode electrostatic force microscopy of non-planar samples [8].…”
Section: Introductionmentioning
confidence: 99%
“…The use of coated or customized tips broadens the usage of the technique for different measurements such as magnetic, elastic, binding forces, and surface potentials. [79][80][81][82][83][84] Moreover, different modes of AFM contribute vital insights into the complexity of biomolecular interactions. [85] Also, this technique facilitates the detection of biomolecules or cells, which makes it a fast biodiagnostic equipment for diseases like cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Such magnetic measurements performed on dried powders or colloidal suspensions are necessary for optimizing the chemical synthesis, as well as for concluding about the magnetic state. MFM on the other hand is a technique able to image individual clusters and to address their magnetization states at the nanometer scale. This technique has been used for revealing magnetic properties of individual NPs and of magnetically correlated grain systems . Nevertheless, MFM has also the potential to qualitatively investigate the magnetization state of clusters made of several NPs, in addition to their morphology, size characteristics, and separation. , Moreover, in some cases, the magnetic interaction forces measured by the microscope can also be used for quantitative magnetization studies under magnetic fields. , …”
Section: Introductionmentioning
confidence: 99%